XIII. Blockchain Technology Implementation for Traceability in the Food Supply Chain – Case Research - Balaic, Marina; Bobek, Samo; Lazović, Vujica; Sternad Zabukovšek, Simona (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
Food supply chains are evolving into coordinated systems, prompting competition between companies and entire supply networks. In this context, Short Food Supply Chains (SFSCs) have emerged as a response to public concerns about food sourcing and handling. Defined by the EU as systems involving few economic actors committed to local development and close producer-consumer relations, SFSCs present both opportunities and challenges. Among key challenges are identity management, transparency, and security. Blockchain technology, introduced shortly after SFSCs gained attention, offers promising solutions by enhancing traceability and linking product information with physical flows. This chapter explores the role of blockchain in addressing traceability challenges and presents a practical case of its application in SFSCs.